Chemical force microscopy with active enzymes. - Fiorini, M (2001)
The adhesion forces have been measured between an atomic force microscope tip derivatized with an active enzyme, shikimate kinase, and an ATP mimic immobilized on a gold surface. Experiments with competitive binding of other ligands in solution show that the observed adhesion forces arise predominantly from specific interactions between the immobilized enzyme and surface-bound adenine derivative. These experiments represent a step in the development of a screening methodology based upon chemical force microscopy.